Association of Left Atrial Function With Mitral Regurgitation: The Atherosclerosis Risk in Communities Study - Chunxiao Zhang; Wendy Wang; Riccardo M. Inciardi; Yuekai Ji; Khaled Shelbaya; Anne Eaton; Alvaro Alonso; Elsayed Z. Soliman; Scott D. Solomon; Amil M. Shah; Lin Yee Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Lower left atrial (LA) function may precede LA enlargement and contribute to mitral regurgitation (MR). We examined the association of LA reservoir strain (a measure of LA function) with MR in the ARIC (Atherosclerosis Risk in Communities) study. Methods We analyzed ARIC participants with echocardiograms at Visits 5 (2011–2013) and 7 (2018–2019). LA reservoir strain was measured at Visit 5. MR was diagnosed by echocardiography. The cross‐sectional association was assessed at Visit 5, and the prospective association was examined through Visit 7 using multivariable logistic regression. Results In the cross‐sectional analysis (n=4689, mean age 75.2±5.0 years, 60.2% female, 19.9% Black), 1927 participants (41.1%) had prevalent MR. Each 1‐SD (7.53%) lower LA reservoir strain was associated with higher odds of prevalent MR (odds ratio [OR], 1.12 [95% CI, 1.04–1.20]). In the prospective analysis (n=1480, mean age 73.5±4.2 years, 54.9% female, 22.6% Black), 409 participants developed MR. A 1‐SD (6.71%) lower LA reservoir strain was associated with higher odds of incident MR (OR, 1.18 [95% CI, 1.04–1.34]); the association was partially attenuated after adjusting for post‐Visit 5 heart failure and atrial fibrillation (OR, 1.14 [95% CI, 1.00–1.30]) and further attenuated after adjusting for LA volume index from Visit 5 (OR, 1.11 [95% CI, 0.98–1.27]). Conclusions LA reservoir strain is associated with prevalent and incident MR in older adults. The association between lower LA reservoir strain and incident MR may be partially explained by LA enlargement, apart from atrial fibrillation and heart failure.